2011
DOI: 10.1038/mt.2010.236
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characteristics of Nanoparticles Determine Their Intracellular Fate in and Processing by Human Blood–Brain Barrier Endothelial Cells In Vitro

Abstract: A polarized layer of endothelial cells that comprises the blood-brain barrier (BBB) precludes access of systemically administered medicines to brain tissue. Consequently, there is a need for drug delivery vehicles that mediate transendothelial transport of such medicines. Endothelial cells use a variety of endocytotic pathways for the internalization of exogenous materials, including clathrin-mediated endocytosis, caveolar endocytosis, and macropinocytosis. The different modes of endocytosis result in the deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
116
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(126 citation statements)
references
References 34 publications
10
116
0
Order By: Relevance
“…52,53 Examination of transcytosis in cell culture models of the BBB show relatively low permeability with prion-labeled NPs (ie, 6% flux) and cationic polyethylenimine-coated NPs (ie, 3.4% flux) after 18-hour permeability studies. 54 These permeability rates are consistent with the low permeability observed for the positively charged AmS-IONPs in the present study.…”
supporting
confidence: 81%
“…52,53 Examination of transcytosis in cell culture models of the BBB show relatively low permeability with prion-labeled NPs (ie, 6% flux) and cationic polyethylenimine-coated NPs (ie, 3.4% flux) after 18-hour permeability studies. 54 These permeability rates are consistent with the low permeability observed for the positively charged AmS-IONPs in the present study.…”
supporting
confidence: 81%
“…There have also been suggestions that surface biomolecules (including adsorbed endogenous proteins) could influence the crossing of biological barriers, such as the blood-brain barrier 35,58,59 . Mastering these phenomena will have deep implications for both nanosafety and nanotherapeutics 4 .…”
mentioning
confidence: 99%
“…It is deemed that the properties of drug delivery vehicles can direct the intracellular processing in brain endothelial cells. Using fixed-size NPs, it has been shown that surface modifications of nanoparticles (e.g., charge and protein ligands) can affect their mode of internalization by BCECs and thereby the subcellular fate (Georgieva et al, 2011).…”
Section: Macromolecular Permeationmentioning
confidence: 99%